2020
DOI: 10.1016/j.ajog.2019.11.554
|View full text |Cite
|
Sign up to set email alerts
|

538: Short interval between IUD removal and conception increases risks for hemorrhage and retained placenta

Abstract: Fetalfractional arm volume is significantly greater in women with GDM compared with NGT, particularly after 32 weeks gestation. This finding is consistent with the characteristic soft tissue accrual (including fat deposition) in the upper part of the fetal body in GDM, which possibly explains the higher occurrence of shoulder dystocia at delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Intrauterine device (IUD) use has been hypothesized as a risk factor for PAS. A retrospective database review reported an association of recent IUD use with PPH and retained placenta, suggesting a possible connection with PAS [48].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Intrauterine device (IUD) use has been hypothesized as a risk factor for PAS. A retrospective database review reported an association of recent IUD use with PPH and retained placenta, suggesting a possible connection with PAS [48].…”
Section: Risk Factorsmentioning
confidence: 99%